Effectiveness of Preventive Safety Management in Building Construction and Oil and Gas Industry - Azizan, Mohammad Arif (IRC, 2015)
The construction industry is well known for its high accident rate and many practitioners consider a preventative approach to be the most important means of bringing about improvements. As employment increases, the number of fatalities occurred also increases. The purpose of this paper is to address previous research and the weaknesses of existing preventative approaches. This study is the first step in improving the percentages of accidents in building construction and oil and gas industry. In addition, this study educate the reader on the implementation of construction safety management system especially in Malaysia and its effectiveness in managing risk and hazards. The research started with gathering information through literature review, in which factors that might affect the standards of construction industry in general were identified. A study questionnaire was then prepared based on this preliminary list of factors. After obtaining and analysing the results of the pilot survey, logistical, technical and other issues or problems have been addressed. In this current study it was found that improvements in many aspects need to be considered and monitored frequently in order to ensure the effectiveness of the safety management system.